REVISITING THE US-CHINA TRADE WAR: A STRATEGIC ASSESSMENT - Mehmood, Zaeem Hassan; Khan, Ramla (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The relations among United States of America and People’s Republic of China have historically survived several bouts and rounds however the approach employed by the Trump Administration for a program involving reprisal hefty tariff-trade war against China has given a new face to the bilateral relations between the two states. The paper demonstrates that domestic and international agents played a vital role in initiating and nurturing the trade clash between Washington and Beijing since 2018 to date. The aim of the study is to ascertain that how the political climate and past pursuits of one country conditions policy outcomes in another, and how domestic political pressures on politician’s conditions their relations with foreign counterparts. The paradigm of rational choice theory is adopted to provide a conceptual understanding to the triggering of the trade war between the economic giants.